Documento sobre retiro de tropas - Todd, Roberto H.; Fernandez, J. Ramón; Jímenez, Alfredo; Rodríguez, Enrique; Morales, Román; Morales, Pablo; Loubriel, Manuel; Calistro Rodríguez, Ramón; Feliú, L.; Rodriguez Bosch, J.; Dávila, Virgilio; Pesquera, José J. (My University, 1899)
Protesta de Bayamón por el retiro de Tropas de Estados Unidos en ese municipio.
Keywords: Davis, George W.